Fostering Parasocial Interaction between Users and Drama Characters through online communities: A Case Study of Ertugrul Ghazi Viewers - Samia Javed; Sumaira Arshad; Muhammad Rawaha Saleem (Journal of Management Practices, Humanities and Social Sciences, 2022)
All of us, at some point in our lives, build an illusionary interaction with our favourite personalities which is all about one-sided affection and admiration for that favorite persona. That interaction is academically named Parasocial interaction. In the past, various studies confirm the impact of drama on its audience and how this impact changes their attitudes and behaviors. This study examines the impact of drama on its audiences' in the context of Parasocial Interaction (PSI). A case study of Ertugrul Ghazi has been taken in this regard as this drama, at the time of research, got the highest viewer ship in Pakistan. This paper revisited parasocial interaction theory and scrutinized PSI between a viewer and the drama character. The paper study the PSI between Facebook group members and drama characters. Qualitative content analysis has been used to explore PSI between social media users (who watch drama series and are also active on Facebook groups for drama series) and drama characters. The themes have been generated and categorized under the level of motivations for PSI e.g., physical, social, and task attraction, and new dimensions for PSI have been explored.